Pengaruh Inflasi, Bi Rate, Kurs Dan CAR Terhadap Profitabilitas Bank Umum Syariah Pada Tahun 2020-2023 - Denavia, Putri; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This consider points to analyze the affect of swelling, BI Rate, trade rate, and Capital Ampleness Proportion (CAR) on the benefit of Islamic commercial banks in Indonesia amid the period of 2020-2023. The strategy utilized may be a quantitative approach with numerous direct relapse investigation, utilizing auxiliary information from the money related articulations of banks enrolled with the Budgetary Administrations Specialist (OJK). The inquire about test comprises of seven Islamic commercial banks that meet particular criteria. The comes about demonstrate that inflation, BI Rate, and trade rate don't have a critical impact on productivity, as measured by Return on Resources (ROA). On the other hand, CAR has been appeared to have a critical affect on the benefit of Islamic commercial banks. Furthermore, at the same time, all four factors essentially impact the benefit of Islamic commercial banks. These discoveries give vital experiences for the administration of Islamic banks in defining techniques to improve money related execution in the midst of changing financial elements. The think about also suggests that future investigate ought to consider other factors which will influence the benefit of Islamic banks to pick up a more comprehensive understanding. Keywords: Inflation, BI Rate, Exchange Rate, Capital Adequacy Ratio, Profitability, Islamic Commercial Banks.